How Do English Teachers Prepare Diagnostic Assessment for Students? Insight from Teachers’ Experiences in an Indonesian Remote Island - Masbara, Abdi; Abduh, Amirullah; Iskandar, Iskandar (Journal of Language Learning and Assessment, 2024)
Purpose This research aims to describe the preparation of diagnostic assessment used by English teachers in an Indonesian remote island in Central Sulawesi.   Methodology This research was conducted at two Junior High Schools located far from the city center of Central Sulawesi. The researcher applied a qualitative case study design. A purposive sampling was used to gain the sample with theory of data saturation. The subject of this research was the three English teachers in the schools that implement Merdeka Curriculum. The data were collected through interview, observation and documentation. The data analysis technique used was thematic analysis.   Results/Findings The result of the research showed that the English teachers prepared the diagnostics assessment by scheduling time of assessment, identifying material of assessment and compiling assessment questions or instrument to be used in the implementation of the diagnostic assessment.   Implications The findings of this research underscore the critical importance of developing a curriculum that effectively supports the implementation of diagnostic assessments. Educational institutions and policymakers are encouraged to leverage these insights to create targeted training programs that enhance teachers’ abilities to design and execute diagnostic evaluations. Furthermore, the study highlights the potential for improving the overall quality of English language instruction in remote areas, as understanding the preparatory processes for diagnostic assessments can enable educators to identify students’ learning needs and tailor their interventions more accurately accordingly. Additionally, the research advocates for the adoption of the best practices in diagnostic assessment preparation, suggesting that other schools, particularly those in similar contexts, could benefit from implementing the successful strategies employed by the teachers at these junior high schools. Finally, this study paves the way for future research into the effectiveness of diagnostic assessments in enhancing student learning outcomes, encouraging subsequent investigations into the relationship between such assessments and academic achievement across diverse educational setting